Fulfillment of Child Support After Parental Divorce: A Comparison of Indonesia and Malaysia - M. Alpi Syahrin; Hellen Last Fitriani; Muhammad Yusrizal Adi Syaputra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Children's rights are an important part of internationally recognized human rights and are guaranteed by national laws, including in Indonesia. Fulfillment of children's rights involves the responsibilities of the government, society, and family, with a focus on civil rights, health, education, and children's participation. One of the main aspects of protecting children's rights is child support, which is the obligation of parents, especially fathers, both in marriage and after divorce. This study aims to analyze the fulfillment of child support after parental divorce from a comparative legal perspective between Indonesia and Malaysia. This study is a normative legal study with a conceptual, comparative, and legislative approach. The results of the study confirm that the comparison between Indonesia and Malaysia shows similarities in basic principles regarding the obligation of fathers to provide support, but there are differences in the law enforcement mechanism. In Malaysia, the sharia court system and the Family Support Agency (BSK) allow deductions from fathers' salaries to ensure payment of support, while in Indonesia, law enforcement depends on the judge's decision. Differences also lie in the position of Islamic law, where Malaysia makes Islam the official state religion, while Indonesia recognizes Islam as a source of legal values, but does not make it a formal state law. Nevertheless, both countries still prioritize the best interests of children in regulating custody and support after divorce.